2020
DOI: 10.3390/life10110302
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term SARS-CoV-2 Infection Associated with Viral Dissemination in Different Body Fluids Including Bile in Two Patients with Acute Cholecystitis

Abstract: Our study aimed to investigate the kinetics of SARS-CoV-2 RNA in bile and in different body fluids of two SARS-CoV-2 positive patients with acute cholecystitis by innovative droplet digital PCR (ddPCR) assays. For each patient, nasopharyngeal- and rectal swabs, bile, urine, and plasma samples were collected at different time points for SARS-CoV-2 RNA quantification by two ddPCR assays. For both patients, ddPCR revealed persistent and prolonged detection of viral RNA in the nasopharyngeal swab despite triple-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…For SARS-CoV-2 RNA quantification by ddPCR, total RNA was extracted from 280 μL of samples using the QIAamp viral RNA mini kit (Qiagen, Hilden, Germany) according to manufacturer’s instruction and concentrated up to 10 μL by using Savant DNA SpeedVac (Thermo Fisher Scientific, Waltham, MA, USA). SARS-CoV-2 RNA was quantified by QX200TM Droplet DigitalTM PCR System (ddPCR, Biorad, Hercules, CA, USA) using an in-house assay, targeting the RdRP gene of SARS-CoV-2 as previously described [ 47 , 48 ]. The assay also targets the housekeeping gene RNAse P as internal control of amplification.…”
Section: Methodsmentioning
confidence: 99%
“…For SARS-CoV-2 RNA quantification by ddPCR, total RNA was extracted from 280 μL of samples using the QIAamp viral RNA mini kit (Qiagen, Hilden, Germany) according to manufacturer’s instruction and concentrated up to 10 μL by using Savant DNA SpeedVac (Thermo Fisher Scientific, Waltham, MA, USA). SARS-CoV-2 RNA was quantified by QX200TM Droplet DigitalTM PCR System (ddPCR, Biorad, Hercules, CA, USA) using an in-house assay, targeting the RdRP gene of SARS-CoV-2 as previously described [ 47 , 48 ]. The assay also targets the housekeeping gene RNAse P as internal control of amplification.…”
Section: Methodsmentioning
confidence: 99%
“…An overall of 3651 samples, from 2825 patients and 145 controls, were extracted from the 39 included studies. The studies were conducted worldwide; 16 in Asia [ 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], 14 in Europe [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and 9 in North America [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. A minority of studies (8) included control samples [ 21 , 28 , 29 , 33 , 38 , 47 , 54 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other commonly used sources were the blood, plasma, saliva, oropharyngeal, sputum, and respiratory excretions. Some studies also reported the use of rectal, urine, and bronchoalveolar lavage (BAL) samples [ 30 , 44 , 45 ]. One study reported using colostrum samples [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from these, COVID-19 is found to trigger arthritis [200], dermatomyositis [131], glioma [188], and early onset of diabetes and severe metabolic complications [33]. Considering the facts that (i) all these NCDs and mental health conditions are found enriched at top ranks in our analysis along with several conditions, (ii) high confidence of our analysis (∼90%), (iii) most of our identified conditions are associated with severity of COVID-19, (iv) the bidirectional relationship between diabetes and COVID-19 [33], psychiatric disorder and COVID-19 [34], COVID-19 and cardiovascular system diseases [35], (v) presence of SARS-CoV-2 viral RNA in patients body for long time after recovery [20], and (vi) our “genetic remittance” assumption [43]; we hypothesize that in long-term, COVID survivors may develop various conditions we have identified in this analysis. However, as COVID-19 is a new disease, long-term observational studies are required on COVID-19 survivors to assess the long-term consequences of the SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, pathways that are activated during the infection remains switched on for a considerable duration within the host and subsequently develop clinical symptoms in long term. The RNA of the SARS-CoV-2 remains active in the COVID-19 survivors for more than 75 days [20] and thus the virus can maintain the upregulation of these omics profile for long periods and as long-term consequences of it, the non-communicable disease (NCD) pathways associated with these upregulated omics profile also remain active and subsequently will trigger the development of the clinical symptoms/phenotypes in long term.…”
Section: Methodsmentioning
confidence: 99%